Principled Criminal Law Reform: Could Macaulay Survive the Age of Governing through Crime? Reflections from the Floor - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 2011)
In response to the detailed discussion of histories and characteristics of codification described in the chapters of this book, these thoughts are designed to identify essential challenges to principled law reform. It is conceded that the political imperatives and pragmatic control agendas driving contemporary criminal law and procedure are more influential in constructing future directions for liability and sanction determinations than the integrity of a principled approach to criminal law, codified or otherwise.